ON THE DURABILITY OF PROGRESSIVE CAVITIES PUMPS - Marius STAN (Fiabilitate şi Durabilitate)
Within this project, it has been demonstrated that the progressive cavities pump flow rate varies depending on the position of the rotor in the stator. These variations, even if they take quite low values, are extremely important because they cause stator heating to record the highest temperatures at 1/3 of the thickness of the elastomer and consequently to stiffen the pump or even damage the pump. Using the hydraulic controller technology, however, by changing its position according to the maximum volume recorded on the length of a stator step, it has been demonstrated that the flow can be uniformized by reducing the range of pulse propagation values